2021
DOI: 10.3389/fimmu.2021.685919
|View full text |Cite
|
Sign up to set email alerts
|

Association Between COVID-19 Pregnant Women Symptoms Severity and Placental Morphologic Features

Abstract: Since the beginning of the pandemic, few papers describe the placenta’s morphological and morphometrical features in SARS-CoV-2–positive pregnant women. Alterations, such as low placental weight, accelerated villous maturation, decidual vasculopathy, infarcts, thrombosis of fetal placental vessels, and chronic histiocytic intervillositis (CHI), have been described.ObjectiveTo analyze clinical data and the placental morphological and morphometric changes of pregnant women infected with SARS-CoV-2 (COVID-19 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 61 publications
8
59
2
2
Order By: Relevance
“…Our study confirmed that a high maternal inflammatory state is possibly contributing to placental insufficiency. As previously stated, we also found that the frequency of placental abnormalities is correlated with the severity of disease [ 49 ]. Although we did not detect SARS-CoV-2 Spike protein in any of the placentas, vertical transmission can still be possible in some cases.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study confirmed that a high maternal inflammatory state is possibly contributing to placental insufficiency. As previously stated, we also found that the frequency of placental abnormalities is correlated with the severity of disease [ 49 ]. Although we did not detect SARS-CoV-2 Spike protein in any of the placentas, vertical transmission can still be possible in some cases.…”
Section: Discussionsupporting
confidence: 78%
“…In line with our study, a recent study found that the deficiency in spiral remodeling was more common in women with SARS-CoV-2 infection than healthy controls. Additionally, the rate of fetal vascular thrombosis was higher in placentas of SARS-CoV-2 infected pregnant compared with healthy controls [ 49 ]. There is emerging evidence that severe SARS-CoV-2 infection is prone to an exaggerated inflammatory response, defined as a cytokine storm [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are reports of an increased risk of stillbirth (18,19), other studies have reported no difference (20,21). There have been reports of an increase in neonatal deaths (7,19); however, in our study, there were no poor pregnancy outcomes, although this is partly by design as women with Active COVID and a poor pregnancy outcome (e.g., a prior fetal death) were not approached to take part in the study.…”
Section: Poor Pregnancy Outcomes and Placental Pathologycontrasting
confidence: 60%
“…There are conflicting data available as to whether the number of Hofbauer cells are increased following maternal SARS-CoV-2 infection. Whilst some studies have found no increase in Hofbauer cell number (7,8), other studies report an increase (9). There are limited data regarding the effect of SARS-CoV-2 infection on T or B lymphocyte numbers, although one study reported no difference following maternal infection (8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 90% of asymptomatic women with C T values less than 25 developed placental fibrinoid compared to no differences in C T values in symptomatic patients. On this matter, Rebutini et al found accentuated but non-significant fibrin deposition in placentas of COVID19 positive women compared to non-COVID19 patients [ 23 ]. This is somewhat similar to our findings.…”
Section: Discussionmentioning
confidence: 99%